2015
DOI: 10.1002/acp.3125
|View full text |Cite
|
Sign up to set email alerts
|

Changed Responses Under Cross‐examination: The Role of Anxiety and Individual Differences in Child Witnesses

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link CROSS-EXAMINATION CHILDREN, ANXIETY, INDIVIDUAL DIFFERENCES AND CROSS-EXAMINATION 2 AbstractThe present study explored whether levels of anxiety, and a range of individual differences measures (age, IQ, and suggestibility), could predict performance during crossexamination questioning. Eighty-three children (aged 4-11 years) witnessed a staged event before being inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
1
5
1
Order By: Relevance
“…Bruck and Melnyk (2004) proposed that perhaps the relation between intelligence and suggestibility is most pronounced for children under the age of eight years. This pattern was not apparent, however, in the present sample (Bettenay, Ridley, Henry, & Crane, 2015;Caprin et al, 2016;Gignac & Powell, 2006;Gilstrap & Papierno, 2004;Gudjonsson et al, 2016;Melinder et al, 2010;Roma, Sabatello, Verrastro, & Ferracuti, 2011). Although there was some evidence of an association between intelligence and suggestibility in two studies with children under the age of 8 years (Bettenay et al, 2015;Gignac & Powell, 2006), another found links in a sample of 8-10-year olds (Roma et al, 2011), and there was no association in the remaining four studies that included children under the age of 8 (6-11-year olds: Caprin et al, 2016; 3-7-year olds: Gilstrap & Papierno, 2004;7-16-year olds: Gudjonsson et al, 2016;4-year olds: Melinder et al, 2010).…”
Section: Cognitive Factorscontrasting
confidence: 87%
See 2 more Smart Citations
“…Bruck and Melnyk (2004) proposed that perhaps the relation between intelligence and suggestibility is most pronounced for children under the age of eight years. This pattern was not apparent, however, in the present sample (Bettenay, Ridley, Henry, & Crane, 2015;Caprin et al, 2016;Gignac & Powell, 2006;Gilstrap & Papierno, 2004;Gudjonsson et al, 2016;Melinder et al, 2010;Roma, Sabatello, Verrastro, & Ferracuti, 2011). Although there was some evidence of an association between intelligence and suggestibility in two studies with children under the age of 8 years (Bettenay et al, 2015;Gignac & Powell, 2006), another found links in a sample of 8-10-year olds (Roma et al, 2011), and there was no association in the remaining four studies that included children under the age of 8 (6-11-year olds: Caprin et al, 2016; 3-7-year olds: Gilstrap & Papierno, 2004;7-16-year olds: Gudjonsson et al, 2016;4-year olds: Melinder et al, 2010).…”
Section: Cognitive Factorscontrasting
confidence: 87%
“…Caprin et al (2016) did not expect to find intelligence differences given that they included only a nonverbal measure of intelligence and expected language to play an important role. In line with this hypothesis, both Bettenay et al (2015) and Gignac and Powell (2006) included combined verbal and nonverbal intelligence measures and found some associations with suggestibility. However, Melinder et al (2010) did not find an association between verbal IQ and suggestibility, and Roma et al (2011) did find links between nonverbal intelligence and suggestibility.…”
Section: Cognitive Factorssupporting
confidence: 57%
See 1 more Smart Citation
“…Further research could explore other potential domains to identify variables which could increase the prediction of eyewitness performance, such as anxiety or suggestibility (e.g. Bettenay, Ridley, Henry, & Crane, 2015). (Note that measures of suggestibility were not relevant for the current study as we did not include leading or misleading questions, nor did we use a misinformation paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…This is perhaps because of an historical attitude that those with ID give inaccurate testimonies and are therefore not viable witnesses (Bowden et al, 2014;Harris and Grace, 1999). Research, however, has demonstrated that this is not true, rather people with ID are able to give accurate evidence under certain conditions (Bettenay et al, 2015;Ericson et al, 1994;Gudjonsson et al, 2000;Henry and Gudjonsson, 1999;Michel et al, 2000). However, the presence of an ID can result in significant communication challenges for a witness when giving evidence in court that can impact on their testimony (Bowles and Sharman, 2014;Gudjonsson and Joyce, 2011).…”
Section: Communication Id and Courtmentioning
confidence: 99%